RECURRENT ACUTE PULMONARY OEDEMA DURING AND AFTER PREGNANCY IN ADRENAL CUSHING: A CASE REPORT - AB, Dorothy Maria; V, Hema Lata; L, Sze Yin; L, Sze Yin; O, Xin Yi; S, Chee Keong (Journal of the ASEAN Federation of Endocrine Societies, 2019)
INTRODUCTION Cushing’s syndrome (CS) during pregnancy is a rare condition and only few cases are reported in literature. Diagnosis and treatment of CS is often difficult. Though most report uncomplicated pregnancy, we report a complicated pregnancy and tumultuous adverse events following delivery. CASE We report a 21-year-old lady who first presented at 23-weeks of gestation with acute pulmonary oedema (APO) requiring non-invasive ventilation and ICU admission. She was investigated for Cushing’s syndrome as she exhibited clinical features of purplish striae, thin skin and easy bruising. Her clinical care was later transferred to another hospital due to logistic issues. Unfortunately at 27-weeks of gestation, she presented with another APO event and hypertensive emergency. She underwent emergency caesarean section during that admission and delivered a 1.1 kg premature baby girl. Postpartum investigation confirmed that she had ACTH independent CS with unsuppressed overnightdexamethasone test cortisol (646 nmol/L), low-dosedexamethasone test cortisol (699 nmol/L) and suppressed ACTH levels (1.1 pmol/L). She was then admitted for another episode of APO after 2-months postpartum. She responded to diuretic therapy and required 3 anti-hypertensive agents. At 4-months postpartum, she developed severe lower back pain which correlated with a T12-L1 compression fracture. As patient was not compliant with follow-up, CTadrenal was only completed at 6-months postpartum after another APO admission. CT-adrenal revealed a 3 cm right medial-limb adrenal adenoma. She is currently awaiting optimisation for right adrenalectomy. CONCLUSION This case highlights the rare occurrence of recurrent APO during pregnancy and postpartum in a patient with adrenal Cushing. The potential link between CS and cardiomyopathy would need further exploration.